MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATERI IPS TEMA PAHLAWANKU KELAS IV SD NEGERI LAMAWAI KABUPATEN FLORES TIMUR - Treesly Y. N Adoe; Andreas Ande; Mahyaman Idris (Universitas Nusa Cendana, 2023)
This study aims to improve student learning outcomes in social studies with the theme of my hero Class IV, SD Negeri Lamawai, East Flores Regency, on historical heritage material from the Hindu, Buddhist, and Islamic periods by applying the Guided Inquiry learning model. The type of research used in this research is Classroom Action Research (CAR) by applying the Guided Inquiry learning model. The data collection method used in this study was to use a sheet of learning achievement tests and observation sheets of teacher and student activities. The results showed that there was an increase in student learning outcomes where in the first cycle the overall percentage of learning completeness only reached 38.09% and in the second cycle there was an increase with the percentage of learning completeness reaching 80.95%. Teacher activity in the first cycle reached 75.00% and in the second cycle, it increased to 91.66%. Student activity also increased from cycle I to cycle II where in cycle I it only reached 68.33% and in cycle II as a whole students reached the very good category with a percentage of 100%. Therefore it can be concluded that the application of the Guided Inquiry learning model to historical material from royal heritage in the Hindu, Buddhist, and Islamic periods can improve student learning outcomes at SD Negeri Lamawai, East Flores Regency.